Interferometric investigation and simulation of refractive index in glass matrixes containing nanoparticles of varying sizes - Feeney, Michael Gerard; Ince, Rabia; Yukselici, Mehmet Hikmet; Allahverdi, Cagdas (OPTICAL SOC AMER, 2011)
The relationship between refractive index and nanoparticle radii of cadmium selenide (CdSe) nanoparticles embedded within glass matrixes was investigated experimentally and by simulations. A homemade automated Michelson interferometer arrangement employing a rotating table and a He-Ne laser source at a wavelength of 632.8 nm determined the refractive index versus nanoparticle radii of embedded cadmium selenide (CdSe) nanoparticles. The refractive index was found to decrease linearly with nanoparticle radius increase. However, one sample showed a step increase in refractive index; on spectroscopic analysis, it was found that its resonant wavelength matched that of the He-Ne source wavelength. The simulations showed that two conditions caused the step increase in refractive index: low plasma frequency and matched sample and source resonances. This simple interferometer setup defines a new method of determining the radii of nanoparticles embedded in substrates and enables refractive index tailoring by modification of exact annealing conditions. (C) 2011 Optical Society of America
Keywords: CDSE; NANOCRYSTALS; RESONANCE; Optics